Effectiveness of Double Discs Synergy Test in the Confirmation of Extended Spectrum Î²-lactamase (ESÎ²L) Production (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
Extended spectrum beta lactamases (ESÎ²Ls) are enzymes which have evolved from bacteria upon exposure to penicillins antibiotics. Such bacteria have developed resistance to Beta lactam antibiotics and their relatives such as cephalosporins (extended spectrum beta lactam antibiotics). The enzymes represent the major source of multidrug resistance in gram negative bacteria. Different methods of confirming ESÎ²L production from bacteria have been described. Most of these methods suggest screening the test isolates in accordance with decrease in susceptibility to extended-spectrum cephalosporins in preliminary susceptibility testing and use any of the available confirmatory tests for ESÎ²L production. However, it is not clear which confirmatory tests are the most sensitive and which extended-spectrum cephalosporins should be tested. In our previous study, disc replacement method was used to detect ESÎ²Ls production among Gram negative isolates from Gombe specialist hospital. In this report, the effectiveness of double disc synergy test (DDST) in the confirmation of ESÎ²L- production was studied from the clinical isolates obtained from this hospital for the first time to the best of our knowledge.  A total of two hundred and fifty (250) bacteria screened to be suspected ESÎ²L-producers were subjected to confirmatory test using double disc synergy test (DDST). The method effectively confirmed ninety six (96) isolates to be ESÎ²L-producers. Esherichia coli had the highest occurrence (26, 27.08%), followed by Klebsiella pneumonia (20, 20.83%), Providencia spp. (14, 14.58%), Morganella morganii (12, 12.5%), Yersinia enterocolitica (6, 6.25%), Pseudomonas aeruginosa , Shigella spp. and Salmonella paratyphi A each with a total occurrence of 4(4.17%), Citrobacter freundii, Serratia marcescens, and Salmonella typhi  each with an occurrence value of 2 (2.08%) while Proteus vulgaris was found to be negative ESÎ²L- producer. In conclusion, the DDST was found to be effective in the confirmation of ESÎ²L-production.
Keywords: extended spectrum Î²-lactamase (esÎ²l), double disc synergy test (ddst), bacterial isolates, penicillins, cephalosporins